Inclusão de parâmetros hidrológicos na avaliação da restauração florestal - Bessi, Débora (2017)
The presence of vegetation cover plays a regulatory role in the water balance through the capture and distribution of rainwater within the compartments of the ecosystem, aiding in the regulation of water flow through the soil, as well as in the process of water supply for the recharge of water bodies. It is possible to say that areas with absence of vegetation and in state of degradation do not present the same effects. Due to the complexity of the biological interactions with the abiotic factors of the environment, the current focus of the environmental recovery is almost exclusive in the biological component, not knowing at what point during the vegetation development, the restoration contributes to the water maintenance, or In what moment and how it will interfere in the water balance of a hydrographic microbasin. The objective of this work was to characterize the behavior of hydrological parameters in forest areas at different stages of restoration by conducting the natural regeneration in order to insert them as a tool to evaluate the restoration. For this purpose, a microbasin was selected within the. (SPP), where three plots of 400 m 2 were demarcated for each treatment, two treatments with different ages of succession (Treatment 1 - 4 years , And Treatment 2 - 10 years) and a fragment without human interference (Treatment 3 - 43 years). The research characterized and evaluated the conditions of natural regeneration through vegetation structure indicators: tree height, trunk diameter, and soil: soil cover by grass and litter, resistance to soil compaction, humidity and Infiltration rate; And luminosity, in addition to the application of diversity and wealth indexes. In each plot, 12 rain gauges were installed and flow through the trunk in all the trees with CAP> 15cm in order to characterize the distribution of the rainfall in the three taratamentos through the hydrological indicators: open precipitation, effective precipitation, internal precipitation, flow through the trunk and interception. The results on vegetation diversity and structure indicated an increasing trend in both number and richness among treatments. It can be said that the species and families present in each treatment are acting in the process of natural succession. The structural characteristics evaluated also demonstrated that the sequence is occurring slowly. Regarding the hydrological parameters, there were significant differences between the three areas studied. It can be noticed that the interception and flow through the trunk have increasing behavior as the natural regeneration progresses, while the internal precipitation and the effective precipitation decrease. These results varied according to the characteristics of the vegetation, for example, the quantity and density of individuals in each plot and species present, besides the climatic characteristics and the precipitations incident on the area. It was possible to observe that with the advancement of the natural succession there was an increase in the vegetal parameters and improvement of the soil parameters, on the other hand, the hydrological parameters showed specific behavior for each treatment, indicating that they are able to respond to the state of maintenance and development of the vegetation.